Conceptual design of a full-standing commercial aircraft seat - Mohamad Dasuki, Norhafizah (2020)
High-density passenger cabin concept has been pursued as one of the approaches to reduce the seat cost per flight, which subsequently lower the flight ticket prices. This trend towards a much denser passenger cabin designs has been observed since 1960s and it is recently further driven by the introduction of low-cost airlines. Thus far, the accommodation of additional passengers inside the same-size aircraft cabin space is often made possible by reducing the seat’s pitch and width. However, this method has possibly reached its maximum potential as many passengers have been complaining of discomforts due to the reduced legroom. Hence to further increase the cabin density, new revolutionary designs of aircraft passenger seat have been explored and among others, this leads to the proposed idea of standing passenger cabin. Although this cabin concept idea has been around for a while, there is no standing passenger cabin design that has been approved by aviation authorities for commercial transport aircraft until now. This can be primarily contributed to the lack of approved designs for the standing passenger seat to be applied in standing cabin implementation and ongoing concerns with safety and comfort aspects of currently proposed standing passenger seat designs. Motivated by this identified research gap, the main goal of this study is to conceptually develop a full-standing passenger seat design that can provide adequate level of safety and comfort to the passengers.